The Effect of Experiential Marketing, Service Quality, and Brand Trust on Repurchase Intention Through Customer Satisfaction As an Intervening Variable: (Case Study on Eiger Users in Wonosobo) - Ranessa Gusvera Dyani; M. Trihudiyatmanto; Eni Candra Nurhayati (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
Purpose - This study aims to analyze, understand, and explain the influence of experiential marketing, service quality, and brand trust on customer satisfaction (a case study of Eiger users in Wonosobo). Methods - This study is quantitative. The population is Eiger users in Wonosobo. The sampling technique used is the formula used by Hair et al. (2019), with a sample size of 120 respondents. Data collection used a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypotheses is Structural Equation Modeling (SEM). Results - This study shows that the variables Experiential Marketing, Service Quality, Brand Trust, and Customer Satisfaction have a positive effect on Repurchase Intention, but Customer Satisfaction cannot mediate the influence of Experiential Marketing, Service Quality, and Brand Trust on Repurchase Intention through Customer Satisfaction. Implications - These findings provide practical implications for companies seeking to strengthen long-term relationship-based marketing strategies by optimizing social media marketing activities. Originality - This research offers a conceptual contribution by positioning social media marketing as a mediating mechanism in the relationship between relationship quality and purchase intention, thereby enriching the literature on relationship marketing in the digital era.